الدولة السعدية من النشأة إلى السقوط دراسة سياسية 916-1069/1510-1659 - مرابطي سعيدة (My University, 2025)
Abstract : At the beginning of the 16th century , the Maghreb Witnessed Significant instability resulting from Liberian invasions on one hand and the decline of the wattasid authority on the other . this led to the weakening of central governance , which became incapable of unifying the region and repelling foreign occupation. This critical situation created an opportunity for the emergence of new leadership in the form of the Saadians . Who succeeded in unifying resistance efforts and organizing campaigns against the Portuguese .their efforts culminated in major victories, most notably the battle of Wadi al-Makhazin (1578), which paved the way for the establishment of the Saadi dynasty and the unification of the territory under their rule. The saadi state reached its peak during the reign of Ahmad al-Mansur, also known as Al- dhahabi (the golden one), he strengthened state institution, ensured internal political stability, and fostered economic prosperity. Under his rule, the state expanded territorially to encompass the entirety of modern-day morocco and parts of west Africa. His foreign policy, characterized by strategic acumen and diplomatic engagement, elevated Morocco’s international standing. however , following his death , the country plunged into a cycle of decline marked by succession plunged into a cycle of decline marked by succession disputes among his heirs , escalating foreign interference , and internal fragmentation , this gradual , disintegration created a power vacuum , enabling the rise of the alaouite dynasty , which consolidated its influence , propagated its legitimacy , and ultimately established a new state on the remnants of the saadi regime . ------------------------------ الملخص : عرف المغرب في بداية القرن السادس عشر جملة من الاضطرابات ناتجة عن الغزو الإيبيري من جهة وضعف السلطة الوطاسية من جهة أخرى ، مما أدى إلى تراجع السلطة المركزية التي أصبحت عامرة عن توحيد البلاد وصد الاحتلال الأجنبي ، هذا الوضع المتأزم فتح المجال لبروز قيادة جديدة ألا وهي السعديون في الجنوب الذين نجحوا في توحيد الصفوف وتنظيم المقاومة ضد البرتغاليين وحققوا انتصارات كبيرة ، أبرزها معركة واد المخازن مما مهد لتأسيس دولتهم وتوحيد البلاد تحت رايتهم . بلغت الدولة السعدية أوج قوتها في عهد المنصور الذهبي ، الذي عزز مؤسسات الدولة وحقق استقرارا داخليا وسياسيا وازدهارا اقتصاديا ومن نفوذها ليشمل كامل التراب المغربي ، وأجزاء من عرب إفريقيا . كما تميزت سياسته الخارجية بالذكاء والانفتاح ، مما عزز مكانة الدولة على الساحة الدولية ، لكن بعد وفاته دخل المغرب في دوامة من التدهور نتيجة الصراع على الحكم بين أبناءه ، إلى جانب تصاعد التدخلات الأجنبية وتفكك النسيج الداخلي ، مما أتاح الفرصة للدولة العلوية بالظهور ، ونشر دعوتها ، واستلام زمام الحكم وتأسيس دولة جديدة على أنقاض . -------------------------------------- Résumé : Au début du XVIe siècle, le Maroc a connu une série de perturbations causées par l'invasion ibérique d'une part et la faiblesse D'autre part, cela a conduit au déclin de l'autorité centrale, qui est devenue déterminée à unifier le pays Cette situation de crise a ouvert la voie à l'émergence d'un nouveau leadership, à savoir les saadiens du Sud, qui Ils ont réussi à unir les rangs et à organiser la résistance contre les Portugais et ont remporté d'importantes victoires, notamment la bataille de Wade Cela a ouvert la voie à la création de leur État et à l'unification du pays sous leur bannière . L'État saadien a atteint l'apogée de sa puissance sous le règne d'al-Mansur al-dhahabi , qui a renforcé les institutions de l'État et atteint la stabilité interne Il est politiquement et économiquement prospère et son influence s'étend à l'ensemble du territoire marocain et à certaines parties de l'Afrique arabe . Sa politique étrangère se distinguait également par son intelligence et son ouverture, ce qui renforçait la position de l'État sur la scène internationale, mais après sa mort, il est entré Le Maroc est dans une spirale descendante en raison du conflit de gouvernance entre ses fils, ainsi que de l'escalade des interventions étrangères Le tissu interne s'est désintégré, ce qui a permis à l'État alaouite d'émerger, de répandre son appel, de reprendre les rênes du gouvernement et d'établir Un nouvel État sur les ruines des saadiens . Signaler un exemple ou une traduction incorrecte
Keywords: السعديين; التراب المغربي; الدولة السعدية; المغرب; بداية القرن السادس عشر; الغزو الإيبيري